Phyto-sociological Studies of Tree Species Outside Forest in Traditional Agroforesty of Chhattisgarh - Sharma, S.B.; Pandey, Samidha; Upadhyaya, S.D.; Agarwal, Rasmi (Indian Journal of Agroforestry, 2020)
The paper deals with the phyto-sociological studies of tree species and physico-chemical properties of soil in traditional Agroforestry of Chhattisgarh (Bilaspur and Raipur Districts), which indicates that the distribution of tree species is contagious and random. Tree species such as Acacia nilotica, Albizia pro cera and Butea monosperma were found to be most successfully grown. The total species diversity, species richness and equitability were 3.975,11.18 and 17.20 respectively. N,Pand K were found to be higher in soils under communities of Acacia nilotica and Albizia procera.